2016
DOI: 10.1007/978-3-319-40515-5_1
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Strategic Decision-Making for Selection of Software Assets

Abstract: Abstract. Companies developing software are constantly striving to gain or keep their competitive advantage on the market. To do so, they should balance what to develop themselves and what to get from elsewhere, which may be software components or software services. These strategic decisions need to be aligned with business objectives and the capabilities and constraints of possible options. These sourcing options include: in-house, COTS, open source and outsourcing. The objective of this paper is to present a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…The solution presented in our previous work is presented as a process [45]. However, based on the validations conducted in the case studies presented here, we concluded that the concept of a common process might not be the best fit to reality.…”
Section: A Decision-making Process-line For Selection Of Software Asset Origins Andmentioning
confidence: 75%
See 3 more Smart Citations
“…The solution presented in our previous work is presented as a process [45]. However, based on the validations conducted in the case studies presented here, we concluded that the concept of a common process might not be the best fit to reality.…”
Section: A Decision-making Process-line For Selection Of Software Asset Origins Andmentioning
confidence: 75%
“…The evaluation is aimed at validating the coverage of the activities represented by the checklist. We also noticed during the validation that the decisionmakers neither executed the decision-making activities orderly nor did they follow the proposed order of execution in our previous work [45].…”
Section: A Decision-making Process-line For Selection Of Software Asset Origins Andmentioning
confidence: 89%
See 2 more Smart Citations
“…Early attempts have been made and preliminary results are available in that regard (cf. Wohlin et al [39]).…”
Section: Criteria (Rq13)mentioning
confidence: 98%